2010
DOI: 10.1016/j.talanta.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Direct amperometric determination of tert-butylhydroquinone in biodiesel

Abstract: The direct amperometric determination of tert-butylhydroquinone (TBHQ) in biodiesel at an unmodified glassy carbon electrode is reported. A biodiesel aliquot was added into an electrochemical cell containing a 75% (v/v) ethanol-water solution under stirring (with final concentration of 50 mmol L(-1) HClO(4)). The amperometric method involved the continuous application of three sequential potential pulses to the working electrode (700 mV for 300 ms, 0 mV for 100 ms and -50 mV for 1s). TBHQ was continuously moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 18 publications
1
17
0
5
Order By: Relevance
“…Previous works have demonstrated that pulsed amperometry is able to solve such a drawback by the application of an additional potential pulse for cleaning the electrode surface from adsorbed oxidation products. 21,22 Thus, a sequence of two pulses was studied taking into consideration the detection of naproxen and the efficient electrode cleaning. This strategy resulted in highly repetitive current responses for naproxen injections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have demonstrated that pulsed amperometry is able to solve such a drawback by the application of an additional potential pulse for cleaning the electrode surface from adsorbed oxidation products. 21,22 Thus, a sequence of two pulses was studied taking into consideration the detection of naproxen and the efficient electrode cleaning. This strategy resulted in highly repetitive current responses for naproxen injections.…”
Section: Resultsmentioning
confidence: 99%
“…20 Pulsed amperometry has also been applied to selective determinations of analytes at electrodes that undergo passivation due to adsorption of electrochemically generated oxidation products. 21,22 In the present study, it is reported an application of BIA with pulsed amperometric detection for fast determination of naproxen in pharmaceutical formulations. The application of two potential pulses provided naproxen detection by its electrochemical oxidation (at +1.5 V for 200 ms) without electrode contamination (+1.0 V for 100 ms for electrode cleaning) using an aqueous electrolyte.…”
Section: Introductionmentioning
confidence: 92%
“…Conforme pode ser observado nas Figuras 1A e 1B, a oxidação do AA a ácido de-hidroascórbico se inicia em torno de +0,50 V, sendo que a corrente de pico obtida foi em torno de +1,00 V. No sentido inverso da varredura (VC), o AA não apresenta sinal de redução, o que caracteriza um processo irreversível nas condições experimentais empregadas. 13 A oxidação do ácido salicílico (AS) a ácido di-hidróxi-benzoico se inicia em aproximadamente +0,95 V, apresentando corrente de pico em +1,20 V. Diferentemente do AA, o AS apresenta um sinal no sentido inverso (VC) da varredura a partir de +0,45 V (redução). No entanto, a corrente de redução é diversas vezes inferior à corrente de oxidação (~20 vezes).…”
Section: Resultsunclassified
“…9 A análise por injeção em fluxo com detecção amperométrica de múltiplos pulsos (FIA-MPA, flow injection analysis and multiple pulse amperometry) 10 é um procedimento de análise que vem sendo explorado na determinação simultânea de compostos empregando um único eletrodo de trabalho, tanto por FIA, 11 como por análise por injeção em batelada (BIA, batch injection analysis). 12 Além de permitir determinações simultâneas, este procedimento também propicia a obtenção de melhor seletividade 13 e precisão, mediante a possibilidade da inclusão de um pulso de potencial que promove limpeza eletroquímica constante 14 ou de empregar o método do padrão interno. 15 Neste trabalho apresenta-se um procedimento simples usando FIA com detecção amperométrica de múltiplos pulsos (MPA) para a determinação simultânea de ácido ascórbico (AA) e ácido acetilsalicílico (AAS) em formulações farmacêuticas.…”
Section: Introductionunclassified
“…87 Os seguintes pulsos de potenciais foram aplicados sobre eletrodo de trabalho de carbono vítreo versus Ag/AgCl em meio de HClO 4 0,05 mol L 1 /etanol (25/75): +0,70 V/300 ms: pulso de potencial aplicado para oxidação e quantificação direta da TBHQ; 0,00 V/100 ms: pulso de potencial aplicado para redução do produto formado pela oxidação da TBHQ em 0,70 V, possibilitando a quantificação indireta do analito; -0,05 V/1000 ms: pulso de potencial aplicado para constante limpeza eletroquímica da superfície do eletrodo de trabalho. O método proposto permite a determinação direta de TBHQ em biodiesel (após simples diluição no eletrólito suporte) com o limite de detecção estimado em 5 µmol L -1 .…”
Section: Análise Indiretaunclassified